Epidemiology of Antibiotic Resistance in Culture-positive Hospitalized Patients in Selected Hospitals in Khartoum, Sudan - Nagwa M. El Amin; Einas A. Osman; Leena Al-Hassan; Ihab B Abdalrahman (Sudan Journal of Medical Sciences)
Objective: To study the prevelence of antibiotic resistance and the prevalent bacterial isolates in hospitalized patients in Khartoum hospitals.